Classification of Maldi-tof Mass Spectrometry Data in the Analysis of Cancer Patients - Małgorzata Plechawska (Штучний інтелект, 2010)
The article presents a case study of Maldi-Tof (Matrix-Assisted Laser Desorption Ionization – Time Of Flight) data analysis and classification. Row mass spectrometry data are preprocessed and decomposed with Gaussian Mixture Model. Gaussian mask is calculated and put at all spectra separately. In further dimension reduction RFE, PLS and T test are used. The classification is done with Support Vector Machine (SVM) method with Gaussian Radial Basis Function kernel. Запропонована класифікація мас-спектрометричних даних медичних досліджень Maldi-Tof, алгоритми та програми комп’ютерного моделювання, які використовуються в проблематиці діагностики і лікування ракових захворювань. Предложена классификация масс-спектрометрических данных медицинских исследований Maldi-Tof, алгоритмы и программы компьютерного моделирования, которые используются в проблемах диагностики и лечения раковых заболеваний.